Tensions between the local and the global: contemporary rural and teaching in rural schools - Elizeu Clementino de Souza; Ana Sueli Teixeira de Pinho; Mariana Martins de Meireles (Universidade Federal de Santa Maria, 2012)
The paper aims to investigate potential tensions between local and global context of contemporary ruralities, emphasizing the times, rhythms and spaces constructed from the experiences of teachers and students in the organization of the routines of rural schools. The paper presents theoretical considerations resulting from two studies in the Graduate Program in Education and Contemporary - PPGEduC / UNEB. The clipping and analysis undertaken focus on education developed in rural areas and tensions present in this context in view, discuss issues concerning the new ruralities contemporary. This discussion has as its central theme the issues of timing and the rhythm in schools with multigrade classes Island Tide that articulates with dilemmas and tensions surrounding the experience lived by teachers of geography of the city engaged in teaching in rural areas in semi-arid region of Bahia. Research has pointed to difficulties faced by rural school to consider the different temporalities that exist in rural areas in their educational processes, as well as difficulties of articulation in these contexts of learning, between the local-global dimensions through which passes the contemporary space. This movement creates stress for teachers' work, since it complicates the relationship between the times established, standardized and rigid, with times of personal students and teachers, covering aspects such as age, life histories, movements and experiences socio-historical and geographical subjects involved in the processes of teaching and learning in rural settings in contemporary times.